STENT THROMBOSIS IN REAL WORLD REGISTRY PATIENTS - Trjacheski, Ted; Brovina, Lulzim; Kostovski, Ognen (Journal of Morphological Sciences, 2018)
Introduction: Many risk factors for stent thrombosis (ST) have been identified, some modifiable and some not. Adequate patient, lesion, and stent selection; a good technical result; and effective treatment are critical in minimizing the risk of ST.In this observational clinical study we tried to elucidate the predictors of ST in real world percutaneous coronary intervention (PCI) patients. Material and methods: Patients who underwent percutaneous coronary interventions with stent implantation were included in a prospective study for 9 months. ST was defined according to Academic Research Consortium for definitive ST.Conditional logistic regression analysis was performed to determine independent predictors.Results: A total of 194 consecutive PCI patients were included in the study. The mean age was 59.37Â±11.04years. After 9 months, the total number of definitive stent thrombosis was 7 (3.6%).In the last model of the multivariate analysis two most powerful predictors of stent thrombosis emerged.In patients who had interrupted DAPT therapy, the risk for stent thrombosis was 4.6 times higher than in the rest of the PCI population and long lesions elevated the risk by 1.28 times (HR: 4.63, 95% CI: 2.64 to 17.63, p= 0.0007); (HR: 1.28, 95% CI: 1.14to 1.56, p= 0.0003), respectively. Conclusions: Stent thrombosis is a multifactorial disease. There is interaction of clinical, angiographic characteristics and also patientâ€™s adherence to treatment.   Risk factors identification obtains possibility to identify patients who would benefit from alternative therapy.